Profil Administratif Kasus TB Paru Di RSU Bunda Thamrin: Tinjauan Jumlah, Durasi Rawat, Dan Pola Pembiayaan Januari - Agustus 2025 - Balqis Damanik (Universitas Ivet, 2025)
Tuberculosis (TB) remains a major challenge within Indonesia’s health care system. This study aims to analyze the administrative profile of inpatient pulmonary TB cases at Bunda Thamrin General Hospital from January to August 2025, focusing on case volume, average length of stay, and payment schemes. The research employed a descriptive quantitative approach using retrospective with secondary data from hospital medical records. A total of 94 TB cases met the inclusion criteria. Findings indicate a fluctuating trend in patient volume, peaking in March 2025. The average length of hospitalization ranged from 5 to 6 days, with the National Health Insurance covering approximately 82% of all cases. The study concludes that the administrative burden of TB care in private hospitals is considerable and requires adaptive management. This research contributes to the understanding of TB service administration in private health facilities and provides evidence to inform health policy strategies aimed at accelerating TB elimination at both local and national levels.